INTERACTIVE METHODS AND ACTIVITIES IN COMMUNICATIVE LANGUAGE TEACHING - Saliyeva Shakhlo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article illustrates some theories and ideas about teaching in an interrogative way that is Communicative language teaching as it is becoming widespread all over the world. Moreover it shows some techniques that can be used in the interactive lessons.